Gerontological Social Work and the Grand Challenges Focusing on Policy and Practice - Sanders, Sara; Kolomer, Stacey R.; Waites Spellman, Cheryl; Rizzo, Victoria M. (Springer International Publishing : Imprint: Springer, 2019)
XX, 186 p. 1 illus.